2014
DOI: 10.1016/j.jtrangeo.2014.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating needs-satisfaction in a discrete choice model of leisure activities

Abstract: In this paper we extend the behavioural scope of discrete choice models for leisure activitytravel choices. More specifically, we investigate to what extent choices for leisure activities and related travels are driven by the satisfaction of needs. In addition to conventional attributes (such as activity costs), our regret based discrete choice model incorporates latent variables representing the anticipated level of individual needs-satisfaction by a particular leisure activity. The latent variables are calib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…In addition, individual characteristics such as age, income, education level, household composition, travel budget, a drivers’ license, and access to a motor vehicle affect mobility behaviour and the level of access to train services [ 9 , 45 47 ]. Specifically, in order to attract potential train riders and increase ridership, train services should be designed according to the level of service preferred by current riders [ 13 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, individual characteristics such as age, income, education level, household composition, travel budget, a drivers’ license, and access to a motor vehicle affect mobility behaviour and the level of access to train services [ 9 , 45 47 ]. Specifically, in order to attract potential train riders and increase ridership, train services should be designed according to the level of service preferred by current riders [ 13 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…By employing an ordered choice model as the latent variable model, the HCM can allow for the ordinal nature of the indicator (e.g. Daly et al 2012;Hess, Shires, and Jopson 2013;Bhat and Dubey 2014;Dekker et al 2014;Soto, Cantillo, and Arellana 2014). However, in order to investigate the nonlinear effect of the latent variable based on an ordered model, a more sophisticated approach has to be developed.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Furthermore, recently, several researchers (e.g. Dekker et al 2014;Hess and Stathopoulos 2014) suggested replacing the utility-maximizing choice model with the random regret minimization model (Chorus, Arentze, and Timmermans 2008) or with a hybrid utility/regret model (Chorus, Rose, and Hensher 2013).…”
Section: The Classic Hcmmentioning
confidence: 99%
See 2 more Smart Citations